Piosenka i życie . Children of Solidarnosc - Lewandowski, Rafael (Kalejdoskop Film Studio, 2006)
Verzio FF Submission In 1980, workers from a Gdansk shipyard began to strike against the totalitarian regime in Poland. A wave of intellectuals joined in and soon the “Solidarity” movement came into being with the mass support of the Polish population. People began to fight for the chance that their children could grow up in a free country with better living conditions and hopes of a better future. After 25 years, this generation of children has grown up. Young people born in the same year as the movement that changed the history of their country give their opinions on the struggle and ideals of their parents. Two generations talk about their ideals of freedom.